Wideband Branch Line Coupler with Open Circuit Coupled Lines - Muataz Watheq Sabri; N A Murad; M K A Rahim (Institute of Advanced Engineering and Science, 2017)
This paper focuses on the design of a Wideband Branch Line Coupler by using open circuits coupled lines technique. The design is implemented by adding four open circuits coupled lines to the structure of the Conventional Branch Line Coupler. The proposed design of Wideband Branch Line Coupler is simulated using CST microwave software. The simulation results show that the coupler is operated at 3.8 GHz with coupling factor of -3dB and 90̊ phase difference between the two output ports. The prototype is fabricated and measured to validate the simulated results. A similar Wide Bandwidth is observed on simulation and measurement. The structure achieved a fractional bandwidth of 42.63%, and return loss of 21 dB compared to the Conventional Branch Line Coupler (BLC).